2020
DOI: 10.1016/j.scitotenv.2020.139280
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown for CoViD-2019 in Milan: What are the effects on air quality?

Abstract: The effect of lockdown on air quality in Milan was assessed.• The trends of 9 pollutants in meteorologically comparable periods were studied. • Lockdown determined a significant reduction of PM 10 , PM 2.5 , BC, benzene, CO and NO x . • SO 2 remained unchanged in the more peripheral areas. • Part of the ozone increase was probably due to the lower NO measured during lockdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

64
436
7
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(517 citation statements)
references
References 25 publications
64
436
7
10
Order By: Relevance
“…Except for the relatively constant level of O 3 for all 3 years, all other CAPs showed clear reductions. These trends are consistent with those in previous studies (Abdullah et al 2020 ; Collivignarelli et al 2020 ; Dantas et al 2020 ; Nakada and Urban 2020 ). In particular, there was a decrease of 24.3% (PM 10 ), 29.6% (PM 2.5 ), 20.0% (NO 2 ), 9.51% (CO), and 11.5% (SO 2 ) between CAP levels in 2020 and the average CAP levels for 2019 and 2018.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Except for the relatively constant level of O 3 for all 3 years, all other CAPs showed clear reductions. These trends are consistent with those in previous studies (Abdullah et al 2020 ; Collivignarelli et al 2020 ; Dantas et al 2020 ; Nakada and Urban 2020 ). In particular, there was a decrease of 24.3% (PM 10 ), 29.6% (PM 2.5 ), 20.0% (NO 2 ), 9.51% (CO), and 11.5% (SO 2 ) between CAP levels in 2020 and the average CAP levels for 2019 and 2018.…”
Section: Resultssupporting
confidence: 93%
“…For instance, the association between the six criteria air pollutants (CAPs: PM 2.5 , PM 10 , SO 2 , CO, NO 2 , and O 3 ) and COVID-19 patients in China has been investigated, and findings suggest that the short-term exposure to air pollutants and the risk of COVID-19 infection showed significant relationships (Zhu et al 2020 ). The lockdown has led to a reduction of air pollutants mainly due to the low density of vehicles circulating in cities such as Milan, Italy, resulting in a sharp decrease in SO 2 and NO x ; however, O 3 concentrations tended to increase because of low NO concentrations in the ambient air (Collivignarelli et al 2020 ). This finding is consistent with another study in Barcelona, Spain (Tobías et al 2020 ), in which O 3 concentrations increased by up to 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Italy (Cristina et al 2020;Muhammad et al 2020;Zambrano-monserrate et al 2020), Spain, France (Muhammad et al 2020;Zambrano-monserrate et al 2020), USA (Muhammad et al 2020), Germany (Zambrano-monserrate et al 2020), Brazil (Dantas et al 2020), Kazakhstan (Kerimray et al 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…A study from China reported that due to the partial effect of unfavorable meteorological conditions, the reduction ratios of PM 2.5 concentrations, as a result of lockdown, were smaller than the reduction ratios of precursor emissions (Wang et al 2020a), indicating the in uence of weather on ambient pollutant concentrations. Even though the major air pollutants, such as PM 2.5 , PM 10 , CO, NO 2 , SO 2 and ammonia (NH 3 ), saw a large reduction in their concentrations, the concentration of ozone (O 3 ) increased during the lockdown period in many parts of the world (Cristina et al 2020;Dantas et al 2020;Mahato et al 2020;Wang et al 2020b). The reason behind this reverse trend of O 3 concentration was identi ed as the decreased PM concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by various scholars have shown how the lockdown has improved the ambient air quality, like in India (Gautam 2020;Mahato et al 2020;Sikarwar and Rani 2020;Srivastava et al 2020), U.S. (Berman and Ebisu 2020), Mexico (Méndez-Arriaga 2020), Kazakhstan (Kerimray et al 2020), Iran (Abdul Halim et al 2018),China (Fan et al 2020; Zambrano-monserrate et al 2020) especially in Wuhan (Cole et al 2020;Lu et al 2020;Sicard et al 2020;Song et al 2016; Q. Wang and Su 2020), Barcelona in Spain (Tobías et al 2020), Sao-Paulo in Brazil (Nakada and Urban 2020), Milan in Italy (Collivignarelli et al 2020), and Salé City in Morocco (Otmani et al 2020) In India, air pollution has become a topic of intense debate at all levels mainly because of the enhanced anthropogenic activities e.g. rapid urbanization, higher population growth, increased energy consumption, and vehicular emission and industrial emission (Dadhich et al 2018;Ghose et al 2005;Gupta et al 2008).…”
Section: Introductionmentioning
confidence: 99%